Link Analysis on Institutional Repository web Network of Indian Institute of Technologies Registered in open DOAR–uncovering Patterns and Trends Hidden in the Network - Kumar, Kutty (International Journal of Knowledge Content Development & Technology, 2018)
The digital libraries of electronic theses and dissertations (ETDs) are promising to be extremely advantageous to scholars especially in developing countries. The ETD initiatives started in India during late nineties and popularity of this concept is growing rapidly in the higher educational and research institutions to disseminate newly emerged knowledge and expertise. Indian Institute of technologies (IIT) has numerous digital libraries each with varying numbers of ETD collections. The purpose of this paper is to critically analyze the network links of Electronic Theses and Dissertation (ETD) repository websites among four IITs. The institutional repositories chosen for the study are IIT Delhi, IIT Hyderabad, IIT Bombay, and IIT Kanpur. The analysis of the study focused on standard graph and network cohesion metrics, such as density, diameter, eccentricity and distances, and clustering coefficient. For an even more detailed analysis of ETD repository websites advanced centrality measures and fast algorithms such as clique census are used. URL: http://ijkcdt.net/xml/14411/14411.pdf